Shoot-out at Broken Bow - West, Charles (Berkley, 2022)
Roy Blanton has raised his four boys in the family business since they were half-pints - and they've gotten away with murder. That is, until U .S. Deputy Marshal Casey Dixon had hot-headed Billy, the youngest, hanged for shooting a policeman. Now the Blantons have vengeance on their minds. Old Buck Avery, Dixon's partner, had been thinking of turning in his badge. And taking down the Blanton name sounds like a fine way to leave the law on a high note. But it's going to get bloody - becauses the houe of Blanton isn't going to fall without a fight.